Impact of Nanoparticles on Oxidative Stress and Inflammatory Pathways in Human Prostate Cancer - Abbood, Sharara Fadhil; Fakhri, Faten Hadi; AlKhafaji, Qatar-Al-Nada M.M (Technium BioChemMed, 2025)
Prostate cancer is one of the most prevalent cancers among men and is fueled by oxidative stress and inflammation that drive tumor progression and resistance to therapy. Production of reactive oxygen species (ROS) and pro-inflammatory cytokine such as tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6) establish a pro-tumor microenvironment. Iron oxide nanoparticles are believed to be promising micro/nano therapy agents because NPs such as ferric oxide (Fe2O3) play a critical role in antioxidant and anti-inflammatory events. Herein, we examine influences of NPs on oxidative stress and inflammatory pathways in prostate cancer models. NP treatment was used for cells exposed to oxidative and inflammatory stressors. We measured a variety of key markers including ROS, MDA, GSH, and activities of antioxidant enzymes (catalase [CAT] and superoxide dismutase [SOD]). The levels of inflammatory cytokines were determined by widely used biochemical methods and spectrophotomedically. This resulted in significant reduction in ROS and MDA (oxidative damage markers) and significant elevation in the reduced GSH levels and these results were supported by the increased levels of antioxidant enzymes namely catalase (CAT) and superoxide dismutase (SOD) activity in NP-treated. Moreover, NPs also inhibited inflammation by downregulating the release of cytokines, such as TNF-α and IL-6. These effects suggest that NPs are capable of restoring oxidative homeostasis and suppressing inflammation, ultimately leading to a more tumor-hostile microenvironment. Abstract Nanoparticles that alleviate oxidative stress and overwrite inflammation pathways synergistically offer two critical blockade points in prostate cancer therapy to counter plasma phase-induced cellular malfunctions required for tumor progression. These results reinforce the prospect of NP as complements to cancer therapy. Optimizing NP formulations could improve their efficacy and safety for potential clinical applications in the future and provide new approaches for improving prostate cancer treatment. CuO NPs with Anti-cancer Effect on Prostate Cancer: In Vivo Study Oxidative Stress along with Inflammation as Potential Pathogenesis Prostate Cancer Responsive Ferric Oxide Nanoparticles Release ROS Assist in Treating Prostate Cancer.